“Access to Education Strategy” in Azerbaijan where Safe Schools Declaration is not endorsed: Compatibility analysis, Prospects and Challenges - Mammadov, Hagverdi; Ismayilova, Nazrin; Udo, Nkoyo (ADA University, 2022)
Education is being attacked around the world, leaving millions of people affected by armed conflict and other violent situations out of reach. During the war, intentional attacks on students, educators, and educational institutions are common. The consequences of long-term conflicts include destruction or damage to educational institutions, unsafe commute and attendance at schools, frequent, long-term, or permanent school closures, loss of teaching materials, opportunities, and educational staff. Weapon contamination and the presence of unused ordinances in and around school facilities can damage or destroy the school's infrastructure, resulting in long-term absences from class (Smith, 2019). Outside of school, children are vulnerable to abuse, exploitation, and recruitment. Being in close proximity to people with weapons, students are exposed to the risk of various abuses, including attacks by hostile forces (ICRC, 2017). The chief risk factor for an attack is the military use of the school as a base, barracks, weapons storage, detention center, which creates the risk of the school being attacked by enemy forces and threatening the safety of its students. Educational institutions have been military occupied or otherwise used by national or non-state armed groups, which makes these institutions lose their civilian character and be targeted as legitimate military objectives, increasing the risk of excessive casualties between students and teachers. While these practices are not prohibited under the IHL, they pose a significant risk to students and staff.
Keywords: Public and International Affairs; Education -- Azerbaijan.; Education strategy -- Azerbaijan.; Schools, Public -- Azerbaijan.